2016
DOI: 10.3389/fonc.2016.00190
|View full text |Cite
|
Sign up to set email alerts
|

LH/hCG-Receptor Expression May Have a Negative Prognostic Value in Low-Risk Endometrial Cancer

Abstract: IntroductionA 51 year-old woman was diagnosed with endometrial cancer (EC) and underwent surgical staging. Pathological evaluation showed a 2 cm × 1 cm G2 endometrioid EC with a 30% myometrial deep invasion (FIGO Stage 1A). The patient was classified as low risk of recurrence, and no adjuvant treatment was offered. Six months after surgery, the patient developed an early vescico-vaginal recurrence, and chemotherapy treatment was started. Few months later, a subsequent involvement of vaginal wall, ileum, and om… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The presence and role of the LH/hCG receptor (LHCG-R) in EC have already been described in previous studies by our group [ 6 – 10 ]. Indeed, our group has already demonstrated that (i) LH/hCG induces an in vitro invasive phenotype, through the activation of LHCG-R and hence of PKA [ 6 ]; (ii) LHCG-R mRNA is expressed in a small cohort primary ECs [ 7 ]; (iii) primary treatment with Gn-RH analogues (aimed to decrease the levels of serum LH) for six years in a patient affected by EC with contraindications to surgery was associated with no evidence of progression of the disease throughout the study period [ 9 ]; and (iv) LHCG-R in a EC preclinical mouse model behaves such as a prometastatic molecular device [ 8 ].…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…The presence and role of the LH/hCG receptor (LHCG-R) in EC have already been described in previous studies by our group [ 6 – 10 ]. Indeed, our group has already demonstrated that (i) LH/hCG induces an in vitro invasive phenotype, through the activation of LHCG-R and hence of PKA [ 6 ]; (ii) LHCG-R mRNA is expressed in a small cohort primary ECs [ 7 ]; (iii) primary treatment with Gn-RH analogues (aimed to decrease the levels of serum LH) for six years in a patient affected by EC with contraindications to surgery was associated with no evidence of progression of the disease throughout the study period [ 9 ]; and (iv) LHCG-R in a EC preclinical mouse model behaves such as a prometastatic molecular device [ 8 ].…”
Section: Discussionmentioning
confidence: 91%
“…The presence of luteinizing hormone/human chorionic gonadotropin receptor (LHCG-R) in EC has already been described in previous studies [ 6 – 10 ], suggesting a key role in cell line proliferation an in invasion in vitro and in preclinical models. Our group demonstrated that LHCG-R acts through its receptor LH-R on the recruitment of protein kinase A (PKA), which induced the activation of beta 1 integrin receptors and the secretion of active matrix metalloproteinase-2 ending in the triggering of cell invasiveness [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Thus LH/hCG can be regarded as a prognostic factor and also a therapeutic target (44). Furthermore, also in patients with low risk of endometrial adenocarcinoma, the expression levels of LH/hCG, analyzed together with other clinicopathological factors, can help to predict recurrence risk in low-risk endometrial adenocarcinoma patients (45).…”
Section: Role Of Hcg In Endometrial Adenocarcinomamentioning
confidence: 99%
“…LH-R was also found to be overexpressed in Endometrial Cancer (EC) cells and its activation by LH promotes local cancer spread and metastatic progression, through the activation of protein kinase A (PKA) 9 . LH-R is overexpressed also in primary EC samples 10 and a high expression level correlates with an early tumor relapse, in a patient with low risk EC 11 . Furthermore, the binding of LH to its receptor increases the metastatic spread of EC cells, in a preclinical menopausal mouse model 12 .…”
Section: Introductionmentioning
confidence: 98%